2014
DOI: 10.1111/1467-9566.12112
|View full text |Cite
|
Sign up to set email alerts
|

Why behavioural health promotion endures despite its failure to reduce health inequities

Abstract: Increasing rates of chronic conditions have resulted in governments targeting health behaviour such as smoking, eating high-fat diets, or physical inactivity known to increase risk for these conditions. In the process, many have become preoccupied with disease prevention policies focused excessively and narrowly on behavioural health-promotion strategies. These aim to improve health status by persuading individuals to change their health behaviour. At the same time, health promotion policy often fails to incor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
262
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 339 publications
(280 citation statements)
references
References 66 publications
5
262
0
4
Order By: Relevance
“…Support was highest for mandatory front-of-pack nutrition labelling for packaged foods. This corresponds with previous research in Australia 5,6,17,18 and elsewhere [19][20][21][22][23][24] which shows greater public support This reflects the ethos of individualism and choice which underpin the dominant neoliberal political ideology, 13 and points to the biopedagogical logics shaping public views. 12 Interestingly, the most common reason for supporting nutrition labels in all socio-demographic groups was to educate other people about nutrition.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Support was highest for mandatory front-of-pack nutrition labelling for packaged foods. This corresponds with previous research in Australia 5,6,17,18 and elsewhere [19][20][21][22][23][24] which shows greater public support This reflects the ethos of individualism and choice which underpin the dominant neoliberal political ideology, 13 and points to the biopedagogical logics shaping public views. 12 Interestingly, the most common reason for supporting nutrition labels in all socio-demographic groups was to educate other people about nutrition.…”
Section: Discussionsupporting
confidence: 88%
“…Under neoliberal governments, Australian obesity prevention efforts have sought to change individuals' behaviours directly through social marketing and other forms of behavioural health promotion which seek to improve knowledge. 13 Our previous work examining public views 7,8 has revealed that, in the prevailing neoliberal context, support for government obesity prevention efforts is often underpinned by beliefs that obesity is caused by a lack of knowledge. While this may translate to strong public support for measures which encourage individuals to take responsibility, 14 public health advocates continue to call for regulations to address the social and commercial determinants of obesity.…”
Section: Introductionmentioning
confidence: 99%
“…16,33 Challenges facing the implementation of broader health promotion include competition with medicine for funding, the medical dominance of health system policy and practice, and the apparent appeal to policymakers of the individualised approach, which poses less strategic and political issues in its implementation, despite evidence for its lack of effectiveness. 34,35 Our research suggests that rigorous evaluation of health sector reforms should be undertaken to assess both intended and unintended outcomes on service quality and delivery. There is a lack of coherence between the policies committed to by governments and the programs and practices that arise.…”
Section: Resultsmentioning
confidence: 98%
“…Despite gradual and sustained improvements in population life-expectancy in developed societies, the issues of sedentary lifestyles and physical inactivity persist as health challenges that are bound up with social inequality (Baum andFisher 2014, Marmot andBell 2012). The fields of public health, health promotion and preventative medicine have identified physical activity as a healthy behaviour with the potential to change patterns of non-communicable diseases such as obesity, diabetes, heart disease and cancer (Warburton et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…However, while physical activity promotion interventions have shown some success in controlled conditions (M€ uller-Riemenschneider et al 2008), their inability to translate into real-world settings has led to calls for more contextualised practice-led research (Reis et al 2016). Public health advocates have also argued for broader changes to the environments in which people move (transport, parks, active living opportunities), yet there has been little exploration into the sociocultural context of embodied experiences of physical (in)activity (Baum and Fisher 2014). We approach this issue by exploring the embodied experiences of parkruna free, regular, citizen-led, community-based, 5 km running event in local parks.…”
Section: Introductionmentioning
confidence: 99%